First molecular characterization of Galba neotropica in Uruguay - Armúa-Fernández, María Teresita; Castro, Oscar; Correa, Oscar; Carvalho, Luis A.; Mangold, Atilio Jose; Sanchís, Jaime; Venzal, José Manuel (2018)
Until recently, it was believed that only two lymnaeid species (i.e. Galba viatrix and Pseudosuccinea columella) occurred in Uruguay. However, based on a molecular approach, an additional species Galba cubensis, was recently discovered. The aim of this study was to molecularly characterize different lymnaeid populations from the northern region of Uruguay. The lymnaeids collections were carried out in two farms of the departments of Paysandú and Tacuarembó. The collected lymnaeids were divided in two fractions, one fraction was used for conchological analyses and detection of trematode larval stages, while the other fraction was used for molecular studies. Three PCRs targeting the 16S, ITS-2 and COI DNA regions were performed and the amplicons obtained were direct sequenced. The sequences were used for homology search and construction of phylogenetic trees by the maximum-likelihood method. The sequencing results revealed that both isolates corresponded to Galba neotropica. The phylogenetic analyses placed our isolates among the G. neotropica monophyletic group, closely related to other isolates of this species found in several South American countries. To our knowledge, this is the first record of G. neotropica in Uruguay and the confirmation as competent intermediate host of Fasciola hepatica. Further studies are needed to define the distribution and the role of each lymnaeid species in the transmission of F. hepatica in Uruguay.